Differences in isoprenoid-mediated energy dissipation pathways between coastal and interior Douglas-fir seedlings in response to drought. (8th November 2019) - Junker-Frohn, Laura Verena; Kleiber, Anita; Jansen, Kirstin; Gessler, Arthur; Kreuzwieser, Jürgen; Ensminger, Ingo
ABSTRACT: Plants have evolved energy dissipation pathways to reduce photooxidative damage under drought when photosynthesis is hampered. Non-volatile and volatile isoprenoids are involved in non-photochemical quenching of excess light energy and scavenging of reactive oxygen species. A better understanding of trees' ability to cope with and withstand drought stress will contribute to mitigate the negative effects of prolonged drought periods expected under future climate conditions. Therefore we investigated if Douglas-fir ( Pseudotsuga menziesii (Mirb.)) provenances from habitats with contrasting water availability reveal intraspecific variation in isoprenoid-mediated energy dissipation pathways. In a controlled drought experiment with 1-year-old seedlings of an interior and a coastal Douglas-fir provenance, we assessed the photosynthetic capacity, pool sizes of non-volatile isoprenoids associated with the photosynthetic apparatus, as well as pool sizes and emission of volatile isoprenoids. We observed variation in the amount and composition of non-volatile and volatile isoprenoids among provenances, which could be linked to variation in photosynthetic capacity under drought. The coastal provenance exhibited an enhanced biosynthesis and emission of volatile isoprenoids, which is likely sustained by generally higher assimilation rates under drought. In contrast, the interior provenance showed an enhanced photoprotection of the photosynthetic apparatus by generally higher amounts of non-volatile isoprenoids and increased amounts of xanthophyll cycle pigments under drought. Our results demonstrate that there is intraspecific variation in isoprenoid-mediated energy dissipation pathways among Douglas-fir provenances, which may be important traits when selecting provenances suitable to grow under future climate conditions.